PENGARUH INFLUENCER KECANTIKAN, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DI SIDOARJO - Monica Cindy Amanda; Misti Hariasih; Satrio Sudarso (MANAJEMEN DEWANTARA, 2026)
This reseach was conducted to determine whether there is an influence of beauty influencers, brand image, and product quality on purchasing decisions for wardah products in Sidoarjo. This research method uses a type of quantitative approach with a population consisting of Wardah product users in Sidoarjo. The sampling technique used a non-probability sampling method through a purposive sampling approach with a total of 100 respondents. The data collection method is through distributing questionnaires and the answers are measured using a Likert scale. Data analysis was carried out with the Partial Least Square - Structural Equation Modeling (PLS-SEM) approach using the SmartPLS 3.0 software analysis tool. The results of this study prove that Beauty Influencers influence Purchasing Decisions for Wardah products in Sidoarjo, Brand Image influences Purchasing Decisions for Wardah products in Sidoarjo, and Product Quality influences Purchasing Decisions for Wardah products in Sidoarjo.